The Impact of Singing Therapy on the Quality of Life of Chronic Obstructive Pulmonary Disease Patients: A Systematic Review - Kim, Hyemin (Advances in Social Sciences Research Journal, 2025)
Purpose: The purpose of this study is to identify the intervention effect on health-related quality of life (HRQoL) of applying singing therapy to Chronic Obstructive Pulmonary Disease (COPD) patients through a systematic review. Method: PubMed, Cochrane, CINAHL, Research Information Sharing Service(RISS), DBpia, and Koreanstudies information service system(KISS) were searched for eligible articles that matched a pre-defined criteria from 2009 to 2023. Four randomized controlled trials (RCTs) were selected for final analysis. The risk of bias assessment was conducted using the assessment criteria adopted from the Cochrane Library. Result: All selected studies used singing therapy as the intervention for treating COPD, but the details of the study such as the time, duration, and frequency varied amongst studies. Also, there was no statistical difference between the intervention and control group on the quality of life. However, in the intervention group, there was a significant difference in the results between pre-intervention and post-intervention. Conclusion: The results from this systematic review implies that singing therapy significantly improves the quality of life in COPD patients.